MENINGKATKAN MINAT BACA SISWA SD KRISTEN NANIA MELALUI PROGRAM LITERASI - Yunitta Wattimena; Sefrin Siang Tangkearung (STKIP Subang, 2026)
Low reading interest in elementary schools is a major challenge in efforts to improve the quality of national literacy. At Nania Christian Elementary School, the phenomenon of low student interest in books requires addressing through a structured program. This study indicates that low reading interest was previously triggered by a reliance on rigid textbooks. As a solution, the literacy program at Nania Christian Elementary School now integrates local literature, such as Maluku folktales, illustrated Bible stories, and contextualized general knowledge for students. This study aims to strengthen the reading interest and skills of Nania Christian Elementary School students. The method used was a descriptive qualitative case study design. The research participants included 22 students at Nania Christian Elementary School. Data were collected through direct observation techniques to record teacher and student actions during the literacy process. Data analysis was conducted qualitatively with reference to classroom action theory. The results of this research confirm that the availability of access, a comfortable atmosphere, and real-life examples (role models) are key to building reading interest. The literacy program is effective in increasing reading interest in Nania Christian Elementary School students, where active involvement between teachers and students creates a more literate and enjoyable learning ecosystem